Comparison of dual task specific training and conventional physical therapy in ambulation of hemiplegic stroke patients: A randomized controlled trial - Muhammad Iqbal; Aatik Arsh; Syed Muhammad Hammad; Ijaz Ul Haq; Haider Darain (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the effectiveness of dual task specific training and conventional physical therapy in ambulation of patients with chronic stroke. Methods: The randomised controlled trial was conducted at the Habib Physiotherapy Complex, Peshawar, Pakistan, from January to August 2017, and comprised patients with chronic stroke. The patients were randomly assigned to two treatment groups. Group A received dual task training, while Group B received conventional physiotherapy. Dual task training included activities such as slowly walking backward, sideways, and forward on a smooth surface while holding a 100gm sandbag. The conventional physiotherapy included mat activities, stretching and strengthening exercises and gait training. Pre-test and post-test data was taken for both spatial and temporal variables for both groups using Time Up and Go Test and 10-meter walk test. Step length, stride length, cycle time and cadence were also calculated before and after treatment. SPSS 23 was used to analyse the data. Results: Of the 64 patients, there were 32(50%) in each of the two groups that both had 17(53%) males and 15(47%) females. Mean age in Group A was 58.28 ± 7.13 years, while in Group B it was 58.87 ± 6.13 years. Baseline parameters had no significant differences between the groups (p>0.05). Post-treatments scores revealed significant improvement of spatial and temporal variable of gait, 10-meter walk, cadence, step length, stride and cycle time in Group A compared to Group B (p<0.05 each). Continuous...